1973
DOI: 10.1111/j.1471-0528.1973.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

INCIDENCE AND DISTRIBUTION OF YEAST SPECIES AND OF TRICHOMONAS VAGINALIS IN THE VAGINA OF PREGNANT WOMEN

Abstract: This paper reports the distribution of yeast-like fungi in 1538 of 6629 vaginal swabs sent for diagnosis of vulvovaginitis over a five-year period, and compares it with the distribution obtaining in two groups of 1031 and 1085 women studied prospectively. C. albicans was isolated from approximately 95 per cent of yeast-containing swabs taken from patients with symptoms or signs of vulvovaginitis and from 75 to 80 per cent of yeast-containing swabs taken from patients being screened in an antenatal booking clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
5
20
1
1
Order By: Relevance
“…glabrata accounted for a further 16%, but other yeasts were uncommon. This distribution is in general agreement with those found by others (Hurley et al, 1972), although some workers have reported, in gynaecological practice, a higher proportion of Tor. glabrata (Timonen et al, 1966;Wilkey, 1967 isolated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…glabrata accounted for a further 16%, but other yeasts were uncommon. This distribution is in general agreement with those found by others (Hurley et al, 1972), although some workers have reported, in gynaecological practice, a higher proportion of Tor. glabrata (Timonen et al, 1966;Wilkey, 1967 isolated.…”
Section: Discussionsupporting
confidence: 93%
“…Many have been undertaken in gynaecological departments, where patients presumably have symptoms and are therefore to some extent selected (Timonen et al, 1966;Diddle et al, 1969). Other investigations have been carried out in antenatal clinics (Hurley et al, 1972), in family planning clinics (Rohatiner and Grimble, 1970), and in general practice (Anyon et al, 1971). The mycological methods used for diagnosis are variable and not always complete (Diddle et al, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…3,6,7,8,9,10 trichomonas vaginalis found to be positive for 228 (43.01%) patients ' candida albicans found to be positive for 206 (38.87%) patients , gardnerella vaginalis found to be positive for 154 ( 29.05%) patients (table II). 11,12,13,14,15 Out of 400 antenatal women of group I, C. trachomatis along with t. vaginalis was found to be positive in 110 (27.50%) women , C. trachomatis along with G. vaginalis was found to be positive in 62 (15.50%) women , T. vaginalis along with G. vaginalis was found to be positive in 42(10.50%) women , candida albicans along with G. vaginalis was found to be positive in 24(6.0%) women , C. trachomatis along with candida albicans was found to be positive in 98 (24.50%) women and T. vaginalis along with candida albicans was found to be positive in 64(16%) women ( table-III)Out of 530 patients of group I, 115 dod not come for follow -up out of 470 patients of group II, 75 did not come for follow -up.…”
Section: Resultsmentioning
confidence: 99%
“…Also Mohr and Herrmann [17] reported in 1972 an incidence of up to 70% in pregnant women. Hurley et al [11] in 1973, on the other hand, found T. vaginalis in only 6% of the pregnant women examined. In his opinion, fungal infections are three times more common in pregnancy.…”
Section: Incidencementioning
confidence: 99%
“…In undiluted vaginal mucus on wood, brass, toilet-paper, towels and bath sponges it survives for 1-2 h and occasionally for 5-6 h. For the mechanism of transmission, see the contribution of Bcdoya (pp. [10][11][12][13][14][15]. Jirovec and Peter [13] are of the opinion that for the typical clinical picture of trichomonas vaginitis to develop, the vaginal flora must first be disturbed by accompanying bacteria.…”
mentioning
confidence: 99%